Ionomic Analysis of Spring Wheat Grain Produced in Kazakhstan and Russia. Issue 7 (12th April 2021) - Abugalieva, Aygul; Flis, Paulina; Shamanin, Vladimir; Savin, Timur; Morgounov, Alexey
ABSTRACT: Spring wheat is produced in Kazakhstan and Western Siberia on a large area exceeding 16 mln ha. The crop grows during the short season from May till September in the extensive production system. The objective of the study was the evaluation of wheat grain for the concentration of macroelements Calcium (Ca), Potassium (K), Magnesium (Mg), Phosphorus (P), and Sulfur (S); toxic heavy metals Arsenium (As), Cadmium (Cd), Chromium (Cr), Lithium (Li), and Lead (Pb), and microelements essential for both plants and humans Copper (Cu), Iron (Fe), Manganese (Mn), Selenium (Se), and Zink (Zn). Samples were collected in 2017 and 2018 from across Kazakhstan and Omsk region. The analysis was conducted at Ionomics Facility at the University of Nottingham. The results demonstrated the high food safety of local grain. Despite the presence of the industry in Aktobe, East Kazakhstan, and Omsk the concentration of toxic metals (As, Cd, Cr, Li, and Pb) were below the limit of quantification or present in minor quantities not likely to affect human health. There was great spatial and yearly variation in the concentrations of macro- and microelements likely to be due to the soil properties, cropping systems, moisture, and other factors. The concentration of essential microelements was similar to wheat grain produced in other countries with exception to Zn. The concentrations of this important element exceeded 50 µg/g in Omsk and East Kazakhstan, above the values targeted by the Harvest Plus biofortification program. Even with the losses of Zn during milling, this grain will be beneficial for human health.